Effects of Electricity Demand on Economic Growth in Nigeria - Osisanwo, Bukonla Grace; Babasanya, Adeyemi O.B.; Ogede, Jimoh Sina; Siyanbola, Adedamola Akeem (NIU Journal of Social Sciences; Vol 9 No 4 (2023): NIU Journal of Social Sciences, Vol. 9 No. 4, December 2023DO - 10.58709/niujss.v9i4.1752, 2023)
The study examined the effects of electricity demand on economic growth over a period of year 2000 to 2022. The objective is to examine the extent to which electricity demand has positively impacted the economic growth. The study utilized the covariance, multi-regression error correction model and Durbin-watson test. The study concluded that there is positive impact of electricity demand on economic growth in Nigeria. The results also show long and short run positive and significant correlation between electricity demand and real gross domestic production, electricity access and RGDP, electricity production from oil, gas and coal and RGDP. This study therefore recommends investment at private and public levels should be encouraged to increase electricity supply to meet with the customers’ rising electricity demands. Finally, government should enforce law directing private operators in distribution electricity to provide prepaid metering system to public institutions, private institutions and the remaining households of the country. Keywords: Economic growth, Electric power Consumption, Electricity access, Electricity demand, Electricity production